2024
DOI: 10.1002/adfm.202312762
|View full text |Cite
|
Sign up to set email alerts
|

Additive‐guided Solvation‐regulated Flame‐retardant Electrolyte Enables High‐voltage Lithium Metal Batteries with Robust Electrode Electrolyte Interphases

Jiandong Liu,
Xin Li,
Junda Huang
et al.

Abstract: Widening the voltage window of the nickel‐rich layered oxide cathode‐based lithium metal batteries (LMBs) can effectively improve the energy density of rechargeable batteries. However, serious safety issues associated with the high reactivity between LiNi0.8Co0.1Mn0.1O2 (NCM811) and electrolyte at high cut‐off voltage remains challenging. Herein, a flame‐retardant electrolyte with the ability to form a robust armor‐like electrode electrolyte interphase (EEI) with LiF and LixByOz compounds for stabilizing Li||N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…4f and j), indicating the involvement of THB in generating LiB x O y inorganic compounds that establish a cross-linked covalent backbone, ensuring the formation of stable and robust SEIs. 43,50 Elemental analyses revealed that the THB was involved in the formation of SEIs enriched in B and F (Fig. S15 and Table S1†).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4f and j), indicating the involvement of THB in generating LiB x O y inorganic compounds that establish a cross-linked covalent backbone, ensuring the formation of stable and robust SEIs. 43,50 Elemental analyses revealed that the THB was involved in the formation of SEIs enriched in B and F (Fig. S15 and Table S1†).…”
Section: Resultsmentioning
confidence: 99%
“…The THB-PDOL forms polymer–inorganic composite SEIs, where the long-chain composition of polymer component enhanced flexibility to the SEI, enabling it to adapt to rapid changes in electrode volume during lithium plating/stripping. 40,50 Additionally, the abundant inorganic component ensures the uniformity of lithium ion transport within the SEI, which is essential for preventing the formation of lithium dendrites on lithium metal anodes.…”
Section: Resultsmentioning
confidence: 99%
“…The electrolyte system exhibits good flame retardancy due to the presence of TEP, while TMB was able to reduce the entry of TEP and PF 6 − into the solvation structure of Li + and inhibit the decomposition of TEP and PF 6 − , stabilizing the structure of NCM811 and inhibiting the dissolution of transition metals and the formation of Li dendrites, which led to the improvement of battery performance. 220 In addition, multifunctional single additives with excellent properties are also the focus of future research. For example, amine-functionalized mesoporous molecular sieve (NASM) additive can construct multifunctional self-reconstructing CEI layers with modified mechanical properties as well as electrochemical stability and simultaneously generate additiveinduced antifluorination protective layer, which can improve the cycling stability of the battery.…”
Section: Improvement Of Electrolytementioning
confidence: 99%
“…Liu et al developed an electrolyte system consisting of fluorinated ethylene carbonate (FEC), ethylmethyl carbonate (EMC), and triethyl phosphate (TEP) as solvents, and trimethyl borate­(TMB) as additives, which were able to build armor-like CEI and SEI. The electrolyte system exhibits good flame retardancy due to the presence of TEP, while TMB was able to reduce the entry of TEP and PF 6 – into the solvation structure of Li + and inhibit the decomposition of TEP and PF 6 – , stabilizing the structure of NCM811 and inhibiting the dissolution of transition metals and the formation of Li dendrites, which led to the improvement of battery performance . In addition, multifunctional single additives with excellent properties are also the focus of future research.…”
Section: Strategy For Regulating Oxygen Precipitation In Nickel-rich ...mentioning
confidence: 99%
“…New energy storage devices with high energy/power density, including supercapacitors (SCs) and lithium metal batteries (LMBs), have obtained increasing interest for the fast development of electric vehicles. Transition-metal selenides (TMSes) have aroused much attention due to their unique optical and electronic properties, making them potential materials for applications in SCs, photocatalysis, and electrocatalysis. Metal–Se bond is weaker than metal–O and metal–S bonds, which is kinetically favored over the conversion reaction; moreover, TMSes possess a special d -electronic structure and adjustable coordination environment. , Hence, TMSes are more suitable as electrode materials for SCs compared with transition-metal oxides/sulfides. Additionally, the electronic conductivity of half-metallic Se is larger than that of nonmetallic S (1 × 10 –5 vs 5 × 10 –28 S m –1 ); therefore, TMSes have gained tremendous attention in the field of SCs .…”
Section: Introductionmentioning
confidence: 99%